2015
DOI: 10.1016/j.molp.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

A Robust CRISPR/Cas9 System for Convenient, High-Efficiency Multiplex Genome Editing in Monocot and Dicot Plants

Abstract: CRISPR/Cas9 genome targeting systems have been applied to a variety of species. However, most CRISPR/Cas9 systems reported for plants can only modify one or a few target sites. Here, we report a robust CRISPR/Cas9 vector system, utilizing a plant codon optimized Cas9 gene, for convenient and high-efficiency multiplex genome editing in monocot and dicot plants. We designed PCR-based procedures to rapidly generate multiple sgRNA expression cassettes, which can be assembled into the binary CRISPR/Cas9 vectors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

32
1,413
4
22

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,714 publications
(1,538 citation statements)
references
References 53 publications
32
1,413
4
22
Order By: Relevance
“…While we were preparing our article, Xing et al (2014) and Ma et al (2015) reported a CRISPR/Cas9 toolkit for targeted mutagenesis in plants. They showed simultaneous knockout of multiple genes in Arabidopsis and rice, which, again, demonstrates the versatility and power of a multiplex CRISPR/Cas9 genome-editing system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While we were preparing our article, Xing et al (2014) and Ma et al (2015) reported a CRISPR/Cas9 toolkit for targeted mutagenesis in plants. They showed simultaneous knockout of multiple genes in Arabidopsis and rice, which, again, demonstrates the versatility and power of a multiplex CRISPR/Cas9 genome-editing system.…”
Section: Discussionmentioning
confidence: 99%
“…First, our comprehensive toolbox is designed for both genome editing and transcriptional regulation. To achieve this, we included four well-characterized Cas9 genes, including the one described by Ma et al (2015), all of which show high activity in plants (Feng et al, 2013;Li et al, 2013;Fauser et al, 2014). Aside from codon optimization, these Cas9 homologs differ from each in epitope tag fusions (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CRISPR‐Cas9 system can be used to achieve multiple mutagenesis by the expression of several sgRNAs targetting different genes (Lowder et al ., 2015; Ma et al ., 2015). The versatility and efficiency of CRISPR‐Cas9 system were also improved by Golden Braid and Gateway‐based vectors (Ma et al ., 2015; Vazquez‐Vilar et al ., 2016) and germ‐line‐specific Cas9 expression (Mao et al ., 2016). One major challenge is the ability of CRISPR‐Cas9 to induce mutations in polyploid genomes, in particular those with closely related subgenomes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the development and customization of plant CRISPR/Cas9 toolboxes or platforms result in more powerful molecular tools for fundamental research and crop breeding (Lowder et al ., 2015; Ma et al ., 2015; Mao et al ., 2016; Tang et al ., 2016; Wang et al ., 2015; Xie et al ., 2015; Xing et al ., 2014). Rice is the most frequently used crop species for testing and applying CRISPR‐Cas9 tools.…”
Section: Introductionmentioning
confidence: 99%